Rhoifolin Suppresses Cell Proliferation and Induces Apoptosis in Hepatocellular Carcinoma Cells In Vitro and In Vivo - Ruolan Chen; Zufa Sabeel; Lu Ying; Youfeng Liang; Rui Guo; Mingxuan Hao; Xiaoyang Chen; Wenjing Zhang; Jian Dong; Yan Liu; Changyuan Yu; Zhao Yang (Pharmaceuticals)
Background: Hepatocellular carcinoma (HCC) is the most prevalent malignant tumor, ranking fifth in terms of fatality with poor prognosis and a low survival rate. Rhoifolin (ROF), a flavonoid constituent, has previously been shown to suppress the proliferation of breast and pancreatic cancer cells. However, its inhibitory effect on HCC has remained unexplored. Objectives: Exploring the potent inhibitory activities and underlying mechanisms of ROF on HCC cells. Methods: The suppressive effect of ROF on HCC cells were assessed via CCK8 assay, apoptosis assay, cell cycle analysis and xenograft tumor mouse model. Furthermore, quantitative real-time PCR and western blot were applied to analyze the underlying mechanisms of ROF on HCC cells. Results: Firstly, the IC50 values of ROF in HepG2 and HuH7 cells were 373.9 and 288.7 µg/mL at 24 h and 208.9 and 218.0 µg/mL at 48 h, respectively. Moreover, the apoptosis rates of HepG2 and HuH7 cells increased from 6.63% and 6.59% to 17.61% and 21.83% at 24 h and increased from 6.63% and 6.59% to 30.04% and 37.90% at 48 h, respectively. Additionally, ROF induced cell cycle arrest at the S phase in HCC cells. Furthermore, ROF suppressed the tumor growth of HCC cells in vivo without obvious toxicity. Mechanically, ROF facilitated apoptosis by upregulating the expression of PIDD1, CASP8, CASP9, BID, BAX, BIM, and BAK1 in HCC cells. Conclusions: ROF significantly restrains the growth of HCC cells in vitro and in vivo, which could be an effective supplement for HCC therapy.